Guidelines for reporting 2017 prevalence sample‐based data in accordance with SSD2 data model. Issue 3 (7th March 2018) - ,; Bocca, Valentina; Boelaert, Frank; Riolo, Francesca; Rizzi, Valentina; Van der Stede, Yves; Stoicescu, Anca‐Violeta
Abstract : Prevalence sample‐based data should be transmitted from Member States to the European Food Safety Authority (EFSA) using the EFSA Standard Sample Description version 2 (SSD2) standard. To support reporting countries in data submission using eXtensible Markup Language (XML) data transfer, specific guidelines are given in this report covering the reporting of sample‐based zoonoses and zoonotic agent data. These guidelines are specifically aimed at guiding the reporting of information under the framework of Directive 2003/99/EC. The objective is to explain in detail the individual data elements that are included in the EFSA (SSD2) data model to be used for the XML prevalence sample based data transmission through the Data Collection Framework according to the protocol described in the EFSA Guidance on Data Exchange (GDE). In particular the data elements to be reported are explained, including information about the data type, a reference to the list of allowed terms and business rules or requirements that may apply.